Construction technologies for nuclear power plants. - Tyobeka, M. (IAEA nuclear energy series ;, 2011)
"This publication serves as a guide to the tools and steps that support plans for constructing nuclear power plants, and consequently improve technical and management skills. It details information on the conventional and recently introduced advanced techniques and methods being used in different aspects of the construction phase of a project, both in the nuclear industry as well as in non-nuclear industries"--Provided by publisher.